Actitudes de prevención de riesgos laborales en trabajadores de transporte de la empresa Cosmos Agencia Marítima SAC Malvinas Cuzco 2022 - Ramirez Bardales, Denzyl Erwin (2024)
cognitive, affective and reactive attitudes and according to the age group and level of education in workers in the transportation of the company Cosmos Agencia Marítima SAC Malvinas-Cuzco 2022 The research was quantitative, comparative descriptive and non-experimental in design. The target population was considered to be 68 workers, and the sample was equal to 68 workers. Inclusion and exclusion criteria were taken into account, using the survey as a technique and a ten-item questionnaire as an instrument, the same one that passed the tests. validity using the Aiken Validity index and the two halves test with the Pearson r statistic. The data were analyzed, processed and tabulated using the SPSS v27 statistical package. The results indicate that in general attitudes and according to the age group and level of education, favorable attitudes predominated and then neutral attitudes. In cognitive and affective attitudes there was a predominance of neutral attitudes, and in reactive attitudes, favorable reactive attitudes. There is a similar behavior according to the age group and the level of education in terms of neutral and favorable attitudes in cognitive aspects. affective and reactive The research hypothesis is not rejected in the sense that there are differences in the general, cognitive, affective and reactive attitudes towards the prevention of occupational risks in the transportation workers of the company Cosmos Agencia Marítima SAC The Falklands Cusco in the year 2022